ANALISIS PROGRAM PENGUATAN PENDIDIKAN KARAKTER (PPK) BERBASIS NILAI KEARIFAN LOCAL MAJA LABO DAHU DALAM MEWUJUDKAN PROFIL PELAJAR PANCASILA PADA SMA DI KABUPATEN BIMA - Tati Haryati; A.Gafar Hidayat (Jurnal Terapung : Ilmu - Ilmu Sosial, 2023)
The purpose of this research are; 1) to describe the implementation of a character education strengthening program based on the values of local wisdom "maja labo dahu" in schools; 2) to identify the outcomes of the character education strengthening program based on the values of local wisdom "maja labo dahu" in schools; 3) to examine the progress of the follow-up actions from the character education strengthening program based on the values of local wisdom "maja labo dahu" in schools. The method used is descriptive qualitative by presenting data and information in the form of descriptions and conclusions. Data was collected using interview instruments, observation, and documentation. The data was analyzed using Reduction, Interpretation, and drawing conclusions. The results of this research provide an overview of the implementation of the character education strengthening program in SMAN 1 Palibelo by mapping out the school programs in creating a school culture, intracurricular, cocurricular, and extracurricular learning that support the creation of the Pancasila student profile. The research findings indicate that the Character Education Strengthening Program implemented by SMAN 1 Palibelo is an important step in forming a generation with excellent character, morality, and ethics, by upholding the noble values of "maja labo dahu". With the support of all parties, including the school, parents, and community, there needs to be synergy in supporting the sustainability of the program, so that the participants themselves can directly internalize it as a preventive measure against global influences